Prevalence of obesity in students aged 5 to 9 years old in for rural schools at Ñuble region - Aldea-Medina , Francesca; Gajardo-Lagos , Paz; López-Espinoza , Miguel Ángel (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
Introduction: obesity is a relevant public health problem due to its multiple consequences. This problem has been barely studied in schoolchildren from rural sectors. Objective: determine the prevalence of obesity according to growth patterns with reference to the Ministry of Health (MINSAL), in schoolchildren aged 5-9 years who come from rural areas of the Ñuble region, Chile. Methods: observational, descriptive and transversal study, aimed at 100 schoolchildren from 5-9 years from four rural schools. Weight and height were measured to classify nutritional status according to the growth patterns provided by the Chilean Ministry of Health. The parents answered a questionnaire about the personal history of the student and the family. The data were processed with R, version 4.1.2. Results: the sample was made up of 41 % of children whose guardians reported an age between 30-39 years, 67 % attended high school and 61 % live in a household made up of 2-4 people. In relation to the nutritional status of children, 65 % of the sample was classified with malnutrition due to excess, of which 30 % were evaluated with obesity. 67 % had normal height and 20 % had abdominal obesity. More men were obese (35 %) than women. The prevalence of obesity increases with the age studied or if there is a chronic disease. Conclusions: a high prevalence of obesity is observed in schoolchildren from rural sectors and in some interest groups, which can serve as a guide to reorient prevention and promotion strategies of this disease in these groups